Approximation and online algorithms : 12th International Workshop, WAOA 2014, Wrocław, Poland, September 11-12, 2014, Revised selected papers /: 12th International Workshop, WAOA 2014, Wrocław, Poland, September 11-12, 2014, Revised selected papers. (2015) - Unknown
No abstract available